Lipidomics profiling of human adipose tissue identifies a pattern of lipids associated with fish oil supplementation - Stanley, EG; Jenkins, BJ; Walker, CG; Koulman, A; Browning, L; West, AL; Calder, PC; Jebb, SA; Griffin, JL (American Chemical Society, 2017)
To understand the interaction between diet and health, biomarkers that accurately reflect consumption of foods of perceived health relevance are needed. The aim of this investigation was to use direct infusion–mass spectrometry (DI–MS) lipidomics to determine the effects of fish oil supplementation on lipid profiles of human adipose tissue. Adipose tissue samples from an n-3 polyunsaturated fatty acid (PUFA) supplementation study (n = 66) were analyzed to compare the pattern following supplementation equivalent to zero or four portions of oily fish per week. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were incorporated into highly unsaturated (≥5 double bonds) triglycerides (TGs), phosphocholines, and phosphoethanolamines as well as being detected directly as the nonesterified fatty acid forms. Multivariate statistics demonstrated that phospholipids were the most accurate and sensitive lipids for the assessing EPA and DHA incorporation into adipose tissue. Potential confounding factors (adiposity, age, and sex of the subject) were also considered in the analysis, and adiposity was also associated with an increase in highly unsaturated TGs as a result of incorporation of the n-6 PUFA arachidonic acid. DI–MS provides a high-throughput analysis of fatty acid status that can monitor oily fish consumption, suitable for use in cohort studies.